Alkylguanidines as Inhibitors of K(+) Transport in Isolated Barley Roots - Lepe, Beatriz Gómez (1975)
It has been shown that plants can accumulate K(+) through an energy-dependent process. The effect of alkylguanidines, in particular octylguanidine on the uptake of (86)Rb(+) by excised barley roots (Hordeum vulgare var. Apizaco LV-72), has been studied. (86)Rb(+) was used as tracer of K(+). The uptake of (86)Rb(+) which is linear with time and shows saturation kinetics is inhibited by octylguanidine. Half-maximal inhibition of (86)Rb(+) uptake is attained at 50 μM octylguanidine. Octylguanidine induces a decrease in the V(max) of the process and increases the Km of the system for Rb(+). When the effects of various alkylguanidines were studied, the following order of effectiveness was encountered; octylguanidine = hexilguanidine > butylguanidine > ethylguanidine > guanidine. This suggests that guanidines inhibit Rb(+) uptake by interacting through its positively charged guanidinium group with a Rb(+) carrier while the alkyl chain interacts with the hydrophobic milieu of the membrane.